Four guardians a principled agent view of American civil-military relations - Donnithorne, Jeffrey W. (Johns Hopkins University Press, 2018)
This book explains who the four US military services truly are and why they make and execute policy as they do. The book focuses on American civil-military relationships, explaining why the services imperfectly satisfy their civilian bosses and why the four services think and act so differently from one another. Ultimately, the book offers three independent but mutually reinforcing contributions to the fields of security studies and American civil-military relations. First, it builds on one of the major theoretical approaches to civil-military relations--agency theory--and identifies key conditions under which agency theory best explains military service behavior. Author Jeffrey W. Donnithorne provides a "principled agent" model that finds four unique condition sets that explain civil-military dynamics with new clarity. Second, the book exposes the importance of service culture in civil-military relations and offers a rich yet concise portrait of each of the four US military services: the Army, Navy, Air Force, and Marine Corps. Third, the book offers two important case studies of civil-military policymaking. These two cases demonstrate the principled agent framework in action, while amply revealing the four services as distinctly different political actors. Finally, the book offers both conclusions and implications for today's security environment, suggesting likely pathways where the services will diverge in their approach to current defense issues. With theoretical novelty, empirical depth, and engaging military history, the book aims to reach academics, practitioners, and general readers alike.